Recretional services for the youth in youth clubs - ketfi, yasmina; boussag, Hajira (Journal of Social Sciences and Humanities, 2021)
The purpose of this study is to reveal the role of e-government in the provision of public security services, where the use of information technology is one of the methods of modern administrative development, as the use of this This method involves a series of successive modifications which contribute to increasing the performance of the public security services. And to improve the activities of the institution in the planning of programs and methods. in order to meet the needs of individuals within the organization, as professional scientific methods, through its various programs in different areas of social, economic, psychological, health, cultural and scientific services; Public security service. This is what I wanted to address in my present intervention on: the role of e-government in the delivery of public security services.